The effects of phytocannabinoids in stroke and pharmacology of CBD and TMP co-application in cellular models - Maguire, Ryan (2022)
In an ever ageing population, stroke represents a growing burden on society. After the age of 55, the likelihood of experiencing a stroke increases two-fold. People in this age group are also at a substantially higher risk of developing a disability following a stroke. Numerous studies have demonstrated the involvement of the endocannabinoid system in modulating molecular disturbances associated with stroke. Thus phytocannabinoids that modulate the endocannabinoid system may represent a novel strategy for treating a stroke.